Career Planning for 21st century - Ryan, Jerry; Ryan, Roberta (New York : West Educational Publishing, 1999)
Helps you build a life in which you are living your greatest passions every day, a life of unbelievable richness and meaning. This work explores the basic concepts of life planning, the changing world of careers, and the process of exploring that world. It helps the reader clarify personal values and set both general life goals and career goals.
Includes bibliographical reference and index.
Keywords: Vocational guidance; Career development; Job hunting